A Pharmacometric Comparison of Omadacycline and Tigecycline Epithelial Lining Fluid (ELF) Penetration. (4th October 2017) - Lakota, Elizabeth A; Rodvold, Keith A; Bhavnani, Sujata M; Steenbergen, Judith N; Tzanis, Evan; Ambrose, Paul G; Rubino, Christopher M
Abstract: Background: Omadacycline, a novel aminomethylcycline antibiotic active against Gram-positive and Gram-negative organisms, is in development for the treatment of patients with acute bacterial skin and skin structure infections and community-acquired bacterial pneumonia (CABP). Data from a Phase 1 ELF study were used to develop population PK models to describe the time course of omadacycline and tigecycline in both plasma and ELF. Methods: Subjects were randomized to receive either omadacycline 100 mg IV q12h × 2 doses followed by 100 mg q24h or tigecycline 100 mg IV x 1 then 50 mg q12h (42 and 21 subjects, respectively). Plasma and ELF samples were collected on Day 4 of therapy. Population PK models were fit to the collected data using NONMEN 7.2. The structural models for plasma were based on previously published population PK models [ECCMID 2016, Abstr P1320; AAC 2006; 50:3701–7]. Various structural models were evaluated for the characterization of ELF concentrations. Day 4 total-drug ELF and total- and free-drug plasma AUC values were computed using numeric integration; these data were used to determine ELF penetration ratios. A fixed protein binding estimate (20%) was used for omadacycline while a non-linear function was used to describe tigecycline's protein binding [AAC 2010; 54:5209–13]. Results: Linear three- and two-compartment models with ELF incorporated into the first peripheral compartment best described the omadacycline and tigecycline PK data, respectively. The ELF visual predictive checks displayed in Figure 1 show that the models accurately captured the omadacycline and tigecycline ELF concentration-time profiles. Model-computed omadacycline and tigecycline total-drug ELF AUC to total-drug plasma AUC ratios were 1.54 and 1.16, respectively. Model-computed total-drug ELF AUC to free-drug plasma AUC ratios were 1.93 and 1.87, respectively. Conclusion: Population PK models were successfully developed to characterize the disposition of both omadacycline and tigecycline in plasma and ELF. When assessed relative to free-drug plasma exposures, omadacycline and tigecycline demonstrated similar ELF penetration. Use of these data with PK-PD target attainment analyses will be useful to support omadacycline dose selection for CABP. Disclosures: E. A. Lakota, Paratek Pharmaceuticals: Research Contractor, Research support; K. A. Rodvold, Paratek Pharmaceuticals: Consultant and Investigator, Consulting fee and Research support; S. M. Bhavnani, Paratek Pharmaceuticals: Research Contractor, Research support; J. N. Steenbergen, Paratek Pharmaceuticals: Employee and Shareholder, Salary; E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. G. Ambrose, Paratek Pharmaceuticals: Research Contractor, Research support; C. M. Rubino, Paratek Pharmaceuticals: Research Contractor, Research support